PLXNA2 as a candidate gene in patients with intellectual disability. Issue 12 (29th July 2021) - Altuame, Fadie D.; Shamseldin, Hanan E.; Albatti, Turki H.; Hashem, Mais; Ewida, Nour; Abdulwahab, Firdous; Alkuraya, Fowzan S.
Abstract: Intellectual disability (ID) is one of the most common disabilities in humans. In an effort to contribute to the expanding genetic landscape of ID, we describe a novel autosomal recessive ID candidate gene. Combined autozygome/exome analysis was performed in two unrelated consanguineous families with ID. Each of the two families had a novel homozygous likely deleterious variant in PLXNA2 and displayed the core phenotype of ID. PLXNA2 belongs to a family of transmembrane proteins that function as semaphorin receptors. Sema5A‐PlexinA2 is known to regulate brain development in mouse, and Plxna2 −/− mice display defective associative learning, sociability, and sensorimotor gating. We note the existence of variability in the phenotype among the three patients, including the existence of variable degree of ID, ranging from borderline intellectual functioning to moderate–severe ID, and the presence of cardiac anomalies in only one of the patients. We propose incomplete penetrance as a possible explanation of the observed difference in phenotypes. Future cases will be needed to support the proposed link between PLXNA2 and ID in humans.